Visceral larva migrans caused by Trichuris vulpis. Issue 8 (August 1980) - Sakano, T; Hamamoto, K; Kobayashi, Y; Sakata, Y; Tsuji, M; Usui, T
Abstract : Two brothers with visceral larva migrans caused by Trichuris vulpis were diagnosed after they had been investigated for an eosinophilia. Both patients were almost asymptomatic. The diagnosis of visceral larva migrans was based on the results of immunoelectrophoretic studies and no liver biopsy was performed. After administration of thiabendazole, the number of eosinophils and serum total IgE levels gradually decreased, and the patients have remained well.